Cultural quarters : principles and practice - Roodhouse, Simon (Intellect, 2010)
This definitive book provides a conceptual context for cultural quarters through a detailed discussion concerning the principles of urban design and planning. To examine these issues, the book presents several case studies drawn from Northern England, Ireland and Vienna to position the emergence of specific cultural areas within a historical and social context and the economics of maintaining the respective districts. Extending this investigation, the author provides an explicit analysis of Bolton Borough Council's moves towards establishing a cultural sector in the town centre, with references.